The Simulation of Performance and Emissions from Rapeseed and Soybean Methyl Ester in Different Injection Pressures - Annisa Bhikuning (Automotive Experiences, 2021)
Biodiesel is one of the promising alternative fuels of the future that is environmentally friendly. Biodiesel can be produced from rapeseed, soybeans, coconut oil, jatropha and many others. It is important to analyze the effect of comparison between diesel fuel and biodiesel to study the effect of combustion and emissions of these fuels. In this research, the simulation of combustion and emission is done with Diesel RK. Three fuels are studied; diesel fuel, rapeseed methyl ester (RME) and soybean methyl ester (SME). The engine was simulated at 2000 rpm and the injection pressures were 944, 1191, 1297, 1420 and 1729 bar respectively. The results show that the specific fuel consumption (SFC), particulate matter (PM), and CO2 emissions of diesel fuel are relatively the same for different injection pressures. However, the SFC, PM and CO2 emissions for rapeseed methyl ester and soybean methyl ester decrease with increasing injection pressure. These results can prove that higher injection pressures in diesel engines can improve combustion and reduce emissions of biodiesel fuel as compared to diesel fuel.